Effectiveness of Art Therapy With Adult Clients in 2018—What Progress Has Been Made? - Regev, Dafna; Cohen-Yatziv, Liat (Frontiers in Psychology, 2018)
In the year 2000, an important art therapy literature review addressed an essential question – does art therapy work? It discussed 17 articles dealing with the issue of the effectiveness of art therapy. Two decades later, this research field has extended its scope and is flourishing. Several current reviews of research work have described the broad range of methods implemented today, which includes qualitative and quantitative studies; other reviews have focused on art therapy with specific populations, or by age group. The aim of this systematic literature review is to contribute to the ongoing discussion in the field by exploring the latest studies dealing with the effectiveness of art therapy with a broad scope of adult clients. We conducted a comprehensive search in four databases and review of every quantitative article that has addressed outcome measures in the art therapy field from 2000 to 2017. This paper presents the latest 27 studies in the field that examine the effectiveness of art therapy with adult clients and divides them into seven clinical categories: cancer patients, clients coping with a variety of medical conditions, mental health clients, clients coping with trauma, prison inmates, the elderly and clients who have not been diagnosed with specific issues but face ongoing daily challenges. It underscores the potential effects of art therapy on these seven clinical populations, and recommends the necessary expansions for future research in the field, to enable art therapy research to take further strides forward.